2023
DOI: 10.1063/5.0138205
|View full text |Cite
|
Sign up to set email alerts
|

Structures and properties of uranium–niobium intermetallic compounds under high pressure: A first principles study

Abstract: Metallic uranium-based alloys, with d-transition metals such as Nb, Mo, and Zr, are promising candidates for actinide fuel. For this purpose, their behaviors under changing physical stimuli need to be understood. Here, we systematically investigate U–Nb intermetallic compounds and predict new compound formations under different pressures using the first-principles swarm-intelligence structure searching method. Two new compounds (U1Nb6 and U2Nb1) were identified to be thermodynamically stable at ambient and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
0
0
Order By: Relevance
“…The addition of elements, for example, Zr, Er, Sc, Zn, Ag and Cu, can upgrade the mechanical performance of Al-Mg-based materials [6][7][8][9]. Researchers have shown that Niobium (Nb) also has the potential to enhance the mechanical performance of some compounds and alloys [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of elements, for example, Zr, Er, Sc, Zn, Ag and Cu, can upgrade the mechanical performance of Al-Mg-based materials [6][7][8][9]. Researchers have shown that Niobium (Nb) also has the potential to enhance the mechanical performance of some compounds and alloys [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%